2013
DOI: 10.1063/1.4817257
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic imaging of self-organization in high power impulse magnetron sputtering plasmas

Abstract: Excitation and ionization conditions in traveling ionization zones of high power impulse magnetron sputtering plasmas were investigated using fast camera imaging through interference filters. The images, taken in end-on and side on views using light of selected gas and target atom and ion spectral lines, suggest that ionization zones are regions of enhanced densities of electrons, and excited atoms and ions. Excited atoms and ions of the target material (Al) are strongly concentrated near the target surface. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
53
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 18 publications
11
53
0
Order By: Relevance
“…3). This suggests that spectrally integrated [2][3][4]11 and spectrally selected 19 images show not just regions of enhanced excitation and ionization but regions of elevated electric potential. Images of ionization zones can and should be interpreted as distributions of electric potential and related electron energy.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…3). This suggests that spectrally integrated [2][3][4]11 and spectrally selected 19 images show not just regions of enhanced excitation and ionization but regions of elevated electric potential. Images of ionization zones can and should be interpreted as distributions of electric potential and related electron energy.…”
mentioning
confidence: 99%
“…26 Our observations also indicated a disappearance or "smoothing" of ionization zones at high pressure, or more precisely, at high neutral atom density, which can be achieved even in the pure self-sputtering mode in vacuum. 27 Spectroscopic imaging of ionization zones 19 revealed that the higher the excitation level, the sharper and more spatially limited the visible emission are, which can be interpreted as the shape of the potential hump (Fig. 3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sputtering was done in pure argon with a flow rate of 60 sccm resulting in a pressure of 0.5 Pa. The choice of aluminum allows us to do a direct comparison with images obtained in a recent study of HiPIMS discharges [10]. In fact, the target and magnetron were the same, and the power supply (SIPP by Melec) was simply switched to dc operation.…”
Section: Introductionmentioning
confidence: 99%
“…The generation mechanism of the spokes and their influence on the transport properties are not fully understood yet. Based on these spokes, energetic ions that have been observed in lateral directions to the magnetron target by Lundin et al [21] who explained these energetic species by a generation mechanism based on a two stream instability interacting with the spoke region; v) Anders and Andersson et al [24,25] proposed a model which incorporates a double layer (DL) when the HiPIMS plasma is in the spokes regime. With a DL present the deconfinement and the acceleration of particles to high energies can be explained.…”
Section: Introductionmentioning
confidence: 99%